2021
DOI: 10.3389/fendo.2021.773820
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Induced Insulin Resistance Is Mediated by High Uric Acid in Obese Children and Adolescents

Abstract: ObjectiveThis study aimed to evaluate whether serum uric acid (SUA) plays a mediating role in the development of insulin resistance (IR) in obese children and adolescents.MethodsA total of 369 participants aged 4-17 years with obesity who attended the Nutrition Outpatient Clinic for Obesity at Xinhua Hospital from January 2012 to January 2019 were recruited for this retrospective study. We classified participants into two groups on the basis of HOMA-IR values: the low HOMA-IR group (< 3.16) (n = 222) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…We speculate that the high prevalence of non-Belgian-natives, moderate degree of obesity and the low prevalence of metabolic syndrome in our sample decreased our power to investigate associations between hyperuricemia and components of the metabolic syndrome [23,29,40,44]. In some studies, a threshold effect in the association between SUA and components of the metabolic syndrome was found with strong correlations only in subjects with very high SUA [44].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…We speculate that the high prevalence of non-Belgian-natives, moderate degree of obesity and the low prevalence of metabolic syndrome in our sample decreased our power to investigate associations between hyperuricemia and components of the metabolic syndrome [23,29,40,44]. In some studies, a threshold effect in the association between SUA and components of the metabolic syndrome was found with strong correlations only in subjects with very high SUA [44].…”
Section: Discussionmentioning
confidence: 87%
“…Contrary to most other studies [20,27,38,44], we found no sex bias in hyperuricemia, even when divided by pubertal status, and SUA concentrations did not increase with age, BMI excess or waist circumference/height index. While a sex bias was inconsistent in pediatric obesity studies, the increase with age, BMI or waist circumference was a more constant nding [23,37,38,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity and other insulin-resistant phenotypes are associated with hyperuricaemia [94][95][96]. High uric acid concentration has been suggested to induce endothelial dysfunction via the interaction of high-mobility group box chromosomal protein 1 with the receptor for advanced glycation end products (HMGB1/RAGE pathway).…”
Section: Endothelial Dysfunction Is the Key Driver Of Microvascular Dysfunction In Obesitymentioning
confidence: 99%
“…Uric acid (UA) is a metabolic end-product of purine compounds, normal serum UA level is controlled by the balance between synthesis and excretion of urate. Clinical and epidemiological studies have suggested associations between increased UA level with obesity, hypertension, insulin resistance, dyslipidemia, liver dysfunction, renal dysfunction and gouty arthritis (1)(2)(3)(4)(5)(6)(7)(8), it was indicated that UA is a mediator of metabolic dysfunction (9,10), it also reflects prognosis of some diseases. In recent decades, Hyperuricemia (HUA) has become a common metabolic disorder worldwide.…”
Section: Introductionmentioning
confidence: 99%